Clinical features and major bleeding predictors for 161 fatal cases of COVID-19: A retrospective observational study - Gokhan Alici (Association of Basic Medical Sciences of Federation of Bosnia and Herzegovina, 2021)
The aim of this study was to investigate the patient characteristics and laboratory parameters for COVID-19 non-survivors as well as to find risk factors for major bleeding complications. For this retrospective study, the data of patients who died with COVID-19 in our intensive care unit were collected in the period of March 20 - April 30, 2020. D-dimer, platelet count, C-reactive protein (CRP), troponin, and international normalized ratio (INR) levels were recorded on the 1st, 5th, and 10th days of hospitalization in order to investigate the possible correlation of laboratory parameter changes with in-hospital events. A total of 161 non-survivors patients with COVID-19 were included in the study.  The median age was 69.8±10.9 years, and 95 (59%) of the population were male. Lung-related complications were the most common in-hospital complications. Patients with COVID-19 had in-hospital complications such as major bleeding (39%), hemoptysis (14%), disseminated intravascular coagulation (13%), liver failure (21%), ARDS (85%), acute kidney injury (40%), and myocardial injury (70%). A multiple logistics regression analysis determined that age, hypertension, diabetes mellitus, use of acetylsalicylic acid (ASA) or low molecular weight heparin (LMWH), hemoglobin, D-dimer, INR, and acute kidney injury were independent predictors of major bleeding. Our results showed that a high proportion of COVID-19 non-survivors suffered from major bleeding complications.